Plant diversity and nutrient substances of native edible plant: Case study in Suka Maju and Tamao Villages, Kapuas Hulu District, West Kalimantan, Indonesia - Sulvi Purwayantie; Suryadi. U. E (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Purwayantie S, Suryadi UE. 2020. Plant diversity and nutrient substances of native edible plant: Case study in Suka Maju and Tamao Villages, Kapuas Hulu District, West Kalimantan, Indonesia. Biodiversitas 21: 842-852. The existence of plant diversity which is wild, indigenous and edibles, needs to be preserved. The research locations in Suka Maju and Tamao Village, Kapuas Hulu District, West Kalimantan, Indonesia were chosen based on population density. The purpose of this study was to determine the plant diversity and nutritional potential from both of regions. The study method used sampling survey and the data were analyzed descriptively. The results showed that from a total of 110 plants, the three local plant names were subjected to one species and nine species were found in both locations. So that from 98 plants consisting of 44 fruits (14 of table fruits and 30 fruits of suka-suka), 30 vegetables and mushrooms, 14 seasonings, 7 nuts, 3 cereals, and tuber. The discovery of rare genera reported from West Kalimantan, they are Hydnocarpus sp, Hodgsonia sp, and Hypoxylon spp. The highest proximate content of carbohydrate is from joluk kusuk seeds (C. lacryma jobil), fats from kepayang seeds (P. edule) and dangkuk seeds (Hydnocarpus sp), protein from sengkubak leaves (A. papuana), ash from keranji (Hypoxylon spp) and dangkuk. The highest Fe and Zn mineral content were found from sengkuang fruit (D. dao) and tepus leaves (E. foetidum), respectively. The results of this survey became an initial recommendation in the development of local wisdom for local food security.